The Role of Social Support in Fostering Self-Acceptance Among Mothers of Children with Intellectual Disabilities - Kristiadi, Angela Oktakurnia Rahel; Soetjiningsih, Christiana Hari (Guidance and Counseling Study Program, Pattimura University, 2024)
This study investigates the relationship between social support and self-acceptance among mothers of children with intellectual disabilities. Utilizing a quantitative correlational design, it examines how perceived social support impacts self-acceptance in a sample of 59 mothers at Rumah Pintar Salatiga. The research employs the Multidimensional Scale of Perceived Social Support and Berger’s Self-Acceptance Scale, revealing that while most mothers receive moderate social support, a significant proportion struggle with self-acceptance. A positive correlation (r = 0.228, p < 0.05) was found between social support and self-acceptance, albeit accounting for only 5.2% of the variance in self-acceptance. This suggests that other factors also significantly influence self-acceptance. The findings align with existing literature, indicating the necessity of comprehensive support systems that address both emotional and practical needs. Methodological limitations include reliance on questionnaires distributed through schools without researcher supervision and the exclusion of digital platforms for data collection. The study emphasizes the need for diverse and inclusive data collection methods in future research and calls for more extensive support mechanisms, including counseling and peer support, to enhance the well-being of this often-overlooked population.